The Relationship Between Green Accounting and Environmental Performance with Financial Performance - Rosdiana, Aria (Journal of Economics, Business, and Government Challenges, 2024)
In the current era, economic competition is highly intense. Consequently, companies are striving to enhance their financial performance by generating profits or gains, often without considering environmental management practices that may lead to environmental damage. The purpose of this study was to examine the relationship between green accounting and financial performance, the relationship between environmental performance and financial performance, and the combined impact of green accounting and environmental performance on financial performance. The population for this research consists of energy companies listed on the Indonesia Stock Exchange during the period 2018-2022. The research employs purposive sampling, and based on the specified criteria, a total of 11 companies were selected as samples. The results of this research indicate that green accounting does not have a positive relationship with financial performance. However, environmental performance is positively relationship with financial performance. Moreover, green accounting and environmental performance, when considered simultaneously, exhibit a positive relationship with financial performance measured using return on assets. This finding contributes to understanding the importance of environmental factors in the context of corporate finance, thereby encouraging companies to pay more attention to environmental management practices in their efforts to enhance financial performance.